2017
DOI: 10.1038/s41598-017-07464-6
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stress during flowering and grain filling offsets beneficial impact of elevated CO2 on assimilate partitioning and sink-strength in rice

Abstract: Elevated [CO2] (e[CO2]) environments have been predicted to improve rice yields under future climate. However, a concomitant rise in temperature could negate e[CO2] impact on plants, presenting a serious challenge for crop improvement. High temperature (HT) stress tolerant NL-44 and high yielding basmati Pusa 1121 rice cultivars, were exposed to e[CO2] (from panicle initiation to maturity) and a combination of e[CO2] + HT (from heading to maturity) using field based open top chambers. Elevated [CO2] significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 71 publications
5
82
1
1
Order By: Relevance
“…However, few studies have concentrate efforts to evaluate rice biochemical/physiological responses under high night temperatures (Chaturvedi et al, 2017) and there are scarcity of information about rice plant responses when are submitted to high night supra-optimal temperatures. Different studies have suggested that the amount of NSC mobilization in the post-heading stem could result from sink strength and environment/management (Chen & Wang, 2008;Kim et al, 2011;Li et al, 2017;Morita & Nakano, 2011;Wada et al, 2017;Yang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have concentrate efforts to evaluate rice biochemical/physiological responses under high night temperatures (Chaturvedi et al, 2017) and there are scarcity of information about rice plant responses when are submitted to high night supra-optimal temperatures. Different studies have suggested that the amount of NSC mobilization in the post-heading stem could result from sink strength and environment/management (Chen & Wang, 2008;Kim et al, 2011;Li et al, 2017;Morita & Nakano, 2011;Wada et al, 2017;Yang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when photosynthesis reductions are accelerated leaf senescence is faster, decreasing the sucrose-starch conversion via enzymatic activity and consequently reducing the grain yield and the quality Chaturvedi et al, 2017;You et al, 2017). Considering that starch represents 80-90% of final grain weight, the events involving since grain filling and final yield are associated to assimilates supplied by current photosynthesis and stem NSC remobilization capacity (Yoshida, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have concentrate efforts to evaluate rice biochemical/physiological responses under high night temperatures (Chaturvedi et al, 2017) and there are scarcity of information about rice plant responses when are submitted to high night supra-optimal temperatures. Different studies have suggested that the amount of NSC mobilization in the post-heading stem could result from sink strength and environment/management (Yang et al, 2000;Chen & Wang, 2008;Kim et al, 2011;Morita & Nakano, 2011;Li et al, 2017;Wada et al, 2017).…”
Section: Discussmentioning
confidence: 99%
“…On the other hand, the negative effects from heat stress, especially during initial reproductive phase could lead to decrease the rice grain yield and its components, by increase the spikelets sterility rate, shorter grain filling period and disrupt the sink activity. Take into account the faster leaf senescence associated to accelerate photosynthesis reductions, decreasing in sucrose-starch conversion via enzymatic activity, could reduce the grain yield and the quality Chaturvedi et al, 2017;You et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rice accounts for maximal human consumption as a staple food by three billion people and provides 20% calorie requirement of the world population (Chaturvedi et al 2017, Jasim et al 2018). Although the current production of rice is enough to feed the world population, only 72% of the global demand of rice can be met by 2050, assuming a continuous and steady yield enhancement rate (Ray et al 2013, Srinivasan et al 2017.…”
Section: Introductionmentioning
confidence: 99%